Early Childhood Learning Transformation Methodology: A Systematic Review Of The Literature on Recent Innovations and Trends - Khairiah, Dina; Nasution, Liah Rosdiani (BUHUTS AL ATHFAL: Jurnal Pendidikan dan Anak Usia Dini, 2025)
This systematic literature review investigates the transformation of methodologies in early childhood education (ECE) with a focus on the integration of innovative practices and the latest trends. The study aims to understand how these methodologies adapt to emerging technological advancements, cultural values, and evolving educational needs, particularly in the Indonesian context. Using a Systematic Literature Review (SLR) approach, the research analyzed articles published between 2020 and 2023 from ScienceDirect. The review identified three primary themes: (1) the critical role of social-emotional learning (SEL) through the use of emotionally enriched language and structured physical activities, which enhance children's ability to understand emotions and improve social interactions; (2) the importance of community and familial support systems in fostering resilience and well-being among children, especially those facing adversity; and (3) the significance of culturally responsive education that integrates local wisdom and values into the curriculum, thus making learning more relevant and engaging for diverse cultural contexts. The findings highlight that successful ECE methodologies require a holistic approach that integrates SEL, technology, and culturally sensitive practices to support children's cognitive, social, and emotional development comprehensively. The study's insights offer valuable implications for policymakers, educators, and stakeholders, suggesting that a balanced integration of these elements can lead to more effective and inclusive early childhood education strategies. This research contributes to the body of knowledge by providing a detailed synthesis of current trends and offering recommendations for future improvements in the field of ECE.